The application of cognitive therapy to the management of physical illness - Zafiropoulou-Koutrouba, Anna; Karanikola, Maria (My University, 2004)
Individuals who are affected by a life threatening disease report psychological morbidity due to exposure to the highly traumatic experience of such a diagnosis. They do not only face a life threatening disease, but also a treatment that probably threatens their bodily integrity, their roles, their sexuality and quality of life. Fear of loss and the prospect of death, as well as the possibility of incapacitation make these people psychologically vulnerable, with reactions of anxiety and depression. These reactions can often be alleviated by standard cognitive-behavioral techniques; within the cognitive psychotherapeutic framework. Cognitive strategies focus on changing dysfunctional automatic thoughts, baste beliefs and assumptions, schemas and cognitive distortions. The aim of cognitive therapy is to resolve the cycle: cognition - feelings - behavior, which is believed to cause the psychopathology. In the same time clinicians who are applying cognitive therapy work on beliefs and cognitions that hinder a person's adjustment to illness and its therapy.
Η εφαρμογή της γνωστικής ψυχοθεραπείας στη σωματική ασθένεια
Keywords: Disease; Life threatening disease